A New p‐Terphenyl Derivative from the Mushroom Thelephora vialis. Issue 8 (August 2015) - Liu, Rui; Wang, Ya‐Nan; Xie, Bo‐Jun; Pan, Qin
Abstract One novel p‐terphenyl compound, named vialisyl A (1), was isolated from the fruiting bodies of Thelephora vialis, together with six known compounds, ganbajunin B (2), phenylacetic acid (3), a mixture of ganbajunins D (4) and E (5), and vialinins A (6) and B (7). Their structures were established by extensive analysis of spectroscopic data (including 1H‐ and 13C‐NMR, HSQC, HMBC, 2D‐INADEQUATE) as well as by comparison with literature reports.